Does prior PCI influence the clinical outcome of CABG? - Taggart, D (2009)
Many patients who undergo PCI subsequently undergo CABG. Until recently, however, there has been little data in the literature describing the effect of previous PCI on subsequent CABG outcome in terms of mortality or major adverse cardiovascular events (MACE). There are, for obvious reasons, no randomised trials addressing this question. This article summaries the limited observational evidence which does exist and which consistently reports an increase in hospital mortality and MACE in patients with prior PCI.